Laporan Kasus Serial : Anensefali - Herdiyantini, Mita; Nugraheni, Pramita Anindya; Novitania, Milleniawati Putri; Renagupita, Melani Sinastri; Setiabudi, Martin Panglipuringtyas; Hendrawan, Michelle; Widisaputro, Michael Deni (Universitas Ciputra Surabaya, 2024)
Preface : Anencephaly is one of the most common forms of neural tube defects and is the second most serious congenital abnormality after congenital heart defects. The overall prevalence of Anencephaly in the world is 5.1 per ten thousand births. Case report : The first patient aged 26 years came without complaints when an ultrasound in the second trimester revealed Anencephaly fetal abnormalities and the pregnancy was terminated with vaginal delivery. The second patient aged 28 years came without complaints when an ultrasound in the first trimester revealed Anencephaly fetal abnormalities and a vaginal delivery was carried out. Discussion : Anencephaly is an abnormality in fetal development characterized by the absence of skull bones accompanied by a lack of most or all of the fetal brain tissue. The main risk factors are lack of folic acid consumption which can occur due to drugs that inhibit folate absorption, the body's increased need for folic acid, and lack of food intake. Early detection requires ultrasound, AFP and acetylcholinesterase examination in the second trimester. The recommended prevention is the consumption of folic acid from preparation for pregnancy until the time of pregnancy.